Engineering of an Avidity-Optimized CD19-Specific Parallel Chimeric Antigen Receptor That Delivers Dual CD28 and 4-1BB Co-Stimulation - Halim, Leena; Das, Kushal K.; Larcombe-Young, Daniel; Ajina, Adam; Candelli, Andrea; Benjamin, Reuben; Dillon, Richard; Davies, David M.; Maher, John (Frontiers in Immunology, 2022)
Co-stimulation is critical to the function of chimeric antigen receptor (CAR) T-cells. Previously, we demonstrated that dual co-stimulation can be effectively harnessed by a parallel (p)CAR architecture in which a CD28-containing second generation CAR is co-expressed with a 4-1BB containing chimeric co-stimulatory receptor (CCR). When compared to linear CARs, pCAR-engineered T-cells elicit superior anti-tumor activity in a range of pre-clinical models. Since CD19 is the best validated clinical target for cellular immunotherapy, we evaluated a panel of CD19-specific CAR and pCAR T-cells in this study. First, we generated a panel of single chain antibody fragments (scFvs) by alanine scanning mutagenesis of the CD19-specific FMC63 scFv (VH domain) and these were incorporated into second generation CD28+CD3 CARs. The resulting panel of CAR T-cells demonstrated a broad range of CD19 binding ability and avidity for CD19-expressing tumor cells. Each scFv-modified CAR was then converted into a pCAR by co-expression of an FMC63 scFv-targeted CCR with a 4-1BB endodomain. When compared to second generation CARs that contained an unmodified or mutated FMC63 scFv, each pCAR demonstrated a significant enhancement of tumor re-stimulation potential and IL-2 release, reduced exhaustion marker expression and enhanced therapeutic efficacy in mice with established Nalm-6 leukemic xenografts. These data reinforce the evidence that the pCAR platform delivers enhanced anti-tumor activity through effective provision of dual co-stimulation. Greatest anti-tumor activity was noted for intermediate avidity CAR T-cells and derived pCARs, raising the possibility that effector to target cell avidity is an important determinant of efficacy.